DEVELOPMENT AND CREATION OF STARTUPS FOR THE DEVELOPMENT OF ENTREPRENEURSHIP IN THE CONDITIONS OF INNOVATION AND INFORMATION TECHNOLOGY: PROBLEMS AND SOLUTIONS - Dautova Z. Y.; Beishenalieva L. В. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
This article examines the impact of startups on the formation of the future society. Covers key aspects of startups such as innovation, economic growth, solving social problems, global connectivity and changing business models. Examples of successful startups and their contribution to various areas of life are discussed. The article highlights the role of startups as drivers of change and sources of innovation that shape the future of society. Startups form the intellectual capital of the country and serve as the basis for further dynamic development. Innovative projects are a whole industry. That is why many startups fail and fail to succeed. Having a competent, friendly team is a key factor in thartue success of a startup. The product must be of high quality and meet the needs of the target audience. A good startup should have enough potential for profit and sustainability in the market. Ambition means having an idea and making it a reality. A successful startup founder has the ambition to make the impossible possible and push himself and his team to success.